PERENCANAAN PEMBANGUNAN DESA YANG TEPAT SASARAN MELALUI OPTIMALISASI DANA DESA PADA DESA TIUDAN - Nanda Rizky P; Bintis Ti'anatud Diniati; Muhammad Azizul Qodri; Dafa Aufan Kanzu; Andi Muhammad Tri D (Universitas Muhammadiyah Gorontalo, 2025)
Planning for village development is a crucial step to ensure that village funds are utilized efficiently and appropriately. This study aims to examine how Tiudan Village conducts development planning using methods that involve open community participation, as well as how Village Fund management is implemented at each planning phase. The study employed a qualitative approach, encompassing in-depth interviews and field observations. The findings indicate that the development planning process is carried out in stages, starting with the Hamlet Deliberation (Musyawarah Hamlet), the Village Deliberation (Musyawarah Desa), and finally the development of the Village Work Plan (RKPDes) and Village Budget (APBDes), which contain priority proposals based on urgent needs and available budget capacity. Transparency is promoted through open forums, the use of village social media, bulletin boards, and the preparation of the Village Budget (RAP) and Village Budget (RAB) overseen by the sub-district government. However, several challenges remain, such as differing interests between hamlets, limited funding, and uneven technical capacity among village officials. Overall, Tiudan Village has implemented the development planning process effectively and accountably, although capacity building and coordination are needed to optimize Village Fund management in the future.